A Novel Antenna With Dual Band-Notched Characteristics using Shorting Pin and Z-Shaped Slot on Conductor Backed - Khodaee, M.; Akbari, M.; Zarbakhsh, S. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a novel UWB antenna with dual notched bands is presented. The antenna consists of a square patch and a ground plane with a ?-shaped slot, which increase the bandwidth from 2.7 GHz to 11.3 GHz. To achieve two bands stop, both Z-shaped slot on conductor backed plane and strip ended up a shorting pin are used. The designed antenna has a small size of 15 × 22 mm2 while indicating the band-stop performance in the frequency bands of 3.1 GHz to 3.8 GHz and 5.1 GHz to 6.1 GHz in order.